Compromisso com o Desempenho : Um Desafio - Souza, Vera Lucia De (2000)
The necessities of growing leveIs of performance require innovative approaches m goal management, mo bilizing abilities to face the traditional inefficiency in what concerns human force contribution. The idea of assess human capital, stimulating human labor ratifies this question, as it tries to change the rupture between enterprise and men by a mechmúst sense. Researches conducted by E. E. Lawler IlI, have revealed that the creation of a motivated and comprollÚsed labor force comes from empowerment, achieved by decentralization, information dissellÚnation, knowledge intensification and by the linkage of results and rewards. The humanistic outlook of goal management is a challenge, as it requires a great deal of balance between competitiveness and ethical comprollÚse with workers, which involves providing a new meaIÚng to evaluation concept, only possible by redefining its mo deis and management practices basis. This study analyzes some perceptions of organization reality aspects, wlúch favors improvements in goal management, replacing judgment with dialogue and implementing an ample overview for supporting recognition of decisions and comllÚtment. The results have shown that the utilization/implementation of approaches centered on human dignity in Organizations is not a utopia, but rather, a challenge to manage.